‘No one can serve two masters’: the unity of philosophy and theology in Ricœur’s Early Thought - Aspray, B (De Gruyter Open, 2019)
While the French philosopher Paul Ricœur is not usually thought of as an existentialist, during his early career he engaged deeply with existentialist thought, and published two articles on the relationship between existentialism and Christian faith. Ricœur’s attempts to relate philosophy and theology often led to great personal distress, which he occasionally referred to as “controlled schizophrenia,” in which he struggled to remain faithful to both philosophical and theological discourse without compromising one for the sake of the other. This essay first explores the influence of existentialist philosophy on Ricœur before surveying how Ricœur understood existentialism, and how in his view it transforms the relationship between philosophy and theology. It then shows how Ricœur is ultimately able to retain his “dual allegiance” to both discourses through active hope in how the Christian doctrine of creation ex nihilo testifies to their original and final unity.